2010
DOI: 10.1088/0957-4484/21/20/205203
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state dye-sensitized solar cells based on ZnO nanocrystals

Abstract: We report on the development of solution-processed ZnO-based dye-sensitized solar cells. We fabricate mesoporous ZnO electrodes from sol-gel processed nanoparticles, which are subsequently sensitized with conventional ruthenium complexes and infiltrated with the solid-state hole transporter medium 2, 2', 7, 7'-tetrakis-(N, N-di-p-methoxyphenylamine)-9, 9'-spirobifluorene (spiro-OMeTAD). Starting from ZnO nanorods synthesized from solution, we investigate the porous ZnO film morphology using various precursor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…26 Many investigators have exploited different synthetic methods to prepare Zn 1Àx Sn x O nanocomposites including multistep solvent-based routes such as co-precipitation, [27][28][29] which is used in this study, hydrothermal 30,31 and sol-gel. 32,33 However, to the best of our knowledge, only a few articles have focused on ss-DSSCs with nanocomposite photo-anodes, 34,35 which reported low efficiencies of up to 0.34 and 0.5% for ss-DSSCs based on ZnO only. Herein, we report the photovoltaic performance of ss-DSSCs solar cells based on Zn 1Àx Sn x O nanocomposites photoanodes as an electron-transport layer prepared via the co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…26 Many investigators have exploited different synthetic methods to prepare Zn 1Àx Sn x O nanocomposites including multistep solvent-based routes such as co-precipitation, [27][28][29] which is used in this study, hydrothermal 30,31 and sol-gel. 32,33 However, to the best of our knowledge, only a few articles have focused on ss-DSSCs with nanocomposite photo-anodes, 34,35 which reported low efficiencies of up to 0.34 and 0.5% for ss-DSSCs based on ZnO only. Herein, we report the photovoltaic performance of ss-DSSCs solar cells based on Zn 1Àx Sn x O nanocomposites photoanodes as an electron-transport layer prepared via the co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the Sample A coating (Figure 7), the onset of the reduction of sintered NiO x nanoparticles (sample B) occurs at approximately 2.6 V. 9,47 However, the cathodic current density exchanged by Sample B for the NiO x reduction [potential range 1.3 -2.6 V vs Li + /Li ( Figure 8)], is generally lower than that obtained for sample A (Figure 7). Despite the larger surface area of NiO x electrodes obtained for sample B, (Figure 4b), [55][56][57][58] and for sol-gel deposited coatings, 6b,14b the current density associated with NiO x reduction [Eq. (1)] is approximately two times higher for the microblast deposited sample A, which possesses a larger particle size in the order of several microns ( Figure 2).…”
Section: Electrochemical Properties Of Microblast Deposited Nio Xmentioning
confidence: 99%
“…[ 27 ] The NG was characterized by introducing ultrasonic waves through the water media without sunlight illumination; the corresponding J-V curve showed that the U OC -NG was ∼ 0.019 V and the I NG was ∼ 0.3 pA cm − 2 (the left inset of Figure 3 a). A J-V curve of the NG (Figure 4 a) was recorded when the sunlight was turned on and off.…”
Section: Communicationmentioning
confidence: 99%